1995
DOI: 10.1111/j.1540-8167.1995.tb00445.x
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized, Double‐Blind, Placebo‐Controlled, Dose‐Ranging Study of Dofetilide in Patients with Inducible Sustained Ventricular Tachyarrhythmias

Abstract: We conclude that: (1) dofetilide produces concentration-related IK blocking effects in patients; (2) an incremental dose-ranging study design aids in identifying the range of doses demonstrating electrophysiologic effects and efficacy; (3) a concomitant placebo group provides important data to assess reproducibility of results over time; and (4) further studies of dofetilide's efficacy and toxicity should be conducted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…In addition, dofetilide treatment was associated with a significantly increased rate of successful antitachycardia pacing in ICD patients. These data are consistent with two small studies showing dofetilide was also effective in acutely suppressing inducible sustained ventricular tachycardia during serial electrophysiologic testing in approximately 45% of patients [41,42].…”
Section: Dofetilidesupporting
confidence: 92%
“…In addition, dofetilide treatment was associated with a significantly increased rate of successful antitachycardia pacing in ICD patients. These data are consistent with two small studies showing dofetilide was also effective in acutely suppressing inducible sustained ventricular tachycardia during serial electrophysiologic testing in approximately 45% of patients [41,42].…”
Section: Dofetilidesupporting
confidence: 92%
“…When administered to patients undergoing electrophysiological studies, 19,[47][48][49] the primary effects of dofetilide are seen on the refractory periods of atrial and ventricular muscle. Dofetilide has no effect on PR, QRS, or HV intervals.…”
Section: Clinical Studiesmentioning
confidence: 99%
“…In a small dose-ranging study, Echt et al 49 showed that 8 of 18 patients had suppression of inducible sustained arrhythmia during serial electrophysiologic studies. Bashir et al 48 reported the results of an intravenous dose-ranging study in 41 patients with inducible sustained monomorphic ventricular tachycardia.…”
Section: Ventricular Arrhythmias and Mortality Trialsmentioning
confidence: 99%
“…In a study by Echt et al, 42 24 patients with inducible ventricular tachycardia received an intravenous dose of either placebo or dofetilide in a double-blind, dose-ranging investigation. A series of increasing dofetilide doses was administered in order to achieve plasma concentrations ranging from 0.25 to 4.5 ng/mL.…”
Section: Ventricular Dysrhythmiasmentioning
confidence: 99%